A case of monkeypox coinfection with syphilis in an Ecuadorian HIV positive young male. Issue 52 (March 2023) - Zambrano Sánchez, Patricia Gabriela; Mosquera Moyano, Felipe
Abstract: The current Monkeypox (MPXV) outbreak has put evidence the worrisome trend of an increased prevalence of other sexually transmitted infections (STDs) particularly in the group of Men who have sex with men (MSM). This phenomenon is illustrated through the case of a 24-year-old male living with HIV that after attending a party where potentially unprotected sex was performed developed a painful popular perianal rash. Laboratory examinations performed confirmed the presence of an acute MPXV infection and primary syphilis, receiving pain relief medication and antibiotics with a rapid control of both illnesses. As in many cases during this outbreak, his HIV status was well controlled and thus a further understanding of the sexual practices in the MSM should help design more adequate interventions to prevent the spread of this and other more conventional STIs.